Determinan Pengangguran di Kota Jambi - Hasana; Zulfanetti, Zulfanetti; Syaparuddin, Syaparuddin (Konsentrasi Ekonomi Sumberdaya Alam dan Manusia, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2023)
Abstract The study aims to analyze the phenomena of domestic investment, foreign investment, inflation, total population, and capital expenditure and unemployment in Jambi City.to analyze what factors influence the numring in Jambi City.The data used in this study is secondary data with the type of Time series 2002-2021 data in Jambi City, research data originating from the. Badan Pusat Statistik.Direktoran Jenderal Perimbangan Keuangan, Badan Koordinasi Penanaman Modal and uses e-views 12. Based on the results, it can be seen that partially, PMDN investment and PMA investment have a significant effect on unemployment in Jambi City, while inflation has no significant effect on unemployment in Jambi City and population and capital expenditure have a significant effect on unemployment in Jambi City. Meanwhile, simultaneously the independent variables have an effect on unemployment.